The Effect of Extreme Age, and Gender, on the Pharmacology and Tolerability of Rivaroxaban - An Oral, Direct Factor Xa Inhibitor - Kubitza, Dagmar; Becka, Michael; Mueck, Wolfgang; Zuehlsdorf, Michael (Blood, 2006)
Anticoagulants, such as warfarin, are indicated for a variety of medical conditions, some of which are strongly age dependent. In younger people, the prevalence of many cardiovascular diseases is typically higher in males; however, with increasing age, this difference often resolves. Rivaroxaban (BAY 59-7939) is a novel, oral, direct Factor Xa (FXa) inhibitor in advanced clinical development for the prevention and treatment of thromboembolic disorders. This randomized, single-blind study was performed to investigate the influences of age and gender on the pharmacokinetics (PK), pharmacodynamics (PD), and tolerability of rivaroxaban in healthy subjects. Four subject groups (young males or females, aged 18–45 years, and elderly males or females, aged >75 years) received a single dose of rivaroxaban 10 mg or placebo (N=34). Gender had no effect on the area under the plasma concentration-time curve (AUC), or maximum plasma concentration (Cmax) of rivaroxaban (Table); however, elderly subjects had higher AUC values than young subjects (least-squares mean ratio [LS-mean] 1.41, 90% confidence interval [CI] 1.20–1.66). The Cmax of rivaroxaban was unaffected by age (LS-mean 1.08, 90% CI 0.96–1.25). Total and renal clearance of rivaroxaban correlated positively with creatinine clearance (CrCL), and inversely with age. The patterns of inhibition of FXa activity by rivaroxaban for all groups were mirrored by those of prolongation of prothrombin time (PT); the maximum effect (Emax) of both consistently occurred 2–4 hours after administration and was unaffected by age or gender. In parallel with the PK results, the AUC of the PD effect, from administration of rivaroxaban to the final time point (AUC0-tn), was increased in elderly subjects (inhibition of FXa activity, LS-mean 1.58, 90% Cl 1.32–1.89; prolongation of PT, LS-mean 1.46, 90% Cl 1.29–1.66); however, all values returned to within 10% of baseline 24 hours after administration of rivaroxaban. The AUC0-tn values correlated inversely with CrCL. Rivaroxaban was well tolerated by all groups; the incidence and intensity of adverse events was similar to placebo. In conclusion, these results demonstrate that the observed effect of age on the PK and PD of this rivaroxaban dose - increased AUC in elderly subjects - was largely due to reduced renal function. Gender had virtually no effect on the PK and PD of rivaroxaban, and neither age nor gender affected tolerability. These findings suggest that rivaroxaban, at similar doses, may not require dose adjustment in elderly patients, or for gender. Phase II studies of rivaroxaban for the prevention of venous thromboembolism also suggested that dose adjustment may not be required for age or gender in this indication. However, this will require confirmation in large-scale phase III studies. PK and PD parameters in subjects receiving rivaroxaban 10 mg (n=6 in each group)Young malesYoung femalesElderly malesElderly femalesAUC (μg·h/L)1477/29.971210/12.691839/28.241941/16.15Cmax (μg/L)227.57/18.25209.73/23.95228.80/23.79245.01/18.23Inhibition of FXaEmax (%)50.86/16.8453.99/12.4456.30/6.3960.16/9.01AUC0-tn (%/h)432.76/38.75343.14/24.61613.94/11.09596.48/23.20Prolongation of PTEmax (x-fold)1.62/9.061.69/8.491.66/5.671.75/4.63AUC0-tn (x-fold/h)22.69/28.0915.98/10.4129.77/3.1526.06/17.52Values are geometric means/geometric coefficients of variation (%)